Optical switch based on nonlinear one dimensional photonic band gap material - Kumar A.; Kumar V.; Nautiyal A.; Singh K.S.; Ojha S.P. (My University, 2025)
In this paper we proposed an optical switch based on nonlinear one dimensional photonic band gap material. Polystyrene and SiO2 have been chosen as constituent materials for the proposed optical switch. Propagation of optical waves through these multilayered structures has been studied for different intensities. Simulation of the device and analysis of its performance has been carried out using transfer matrix method. The study shows that the polystyrene/SiO2 based nonlinear photonic band gap material studied here can work as an optical switch. The proposed device could also be useful in OTDM demultiplexing, all optical information processing, etc. Due to its simple geometric structure and simple operating principle, this device could be a strong candidate for the variety of applications in the field of integrated optoelectronics. © 2017 Elsevier GmbH